The Influence of Intrinsic Motivation and Self-Efficacy on The Normative Commitment of Civil Servants at The Department of Manpower and Transmigration, Ketapang Regency - Sudiani, Mery Irma; Mahdi, Irfan (UNIVERSITAS PAKUAN, 2025)
This study aims to determine the effect of intrinsic motivation and self-efficacy on normative commitment among civil servants at the Ketapang Regency Manpower and Transmigration Office. Data were collected from 33 civil servants through questionnaires and direct interviews with the administrative head. Multiple linear regression analysis revealed that intrinsic motivation and self-efficacy simultaneously have a positive and significant effect on normative commitment, with an F-value of 40.874 and significance of 0.000 (0.05). Partially, intrinsic motivation has a significant positive influence with a t-value of 2.633 and significance of 0.009 (0.05), while self-efficacy has a stronger positive influence with a t-value of 3.609 and significance of 0.000 (0.05). The coefficient of determination (R²) of 0.453 indicates that 45.3% of the variation in normative commitment can be explained by the two independent variables, while the remainder is influenced by factors outside the scope of this study. These results emphasize the importance of intrinsic motivation and self-efficacy in enhancing employees' sense of responsibility and loyalty toward the organization. Therefore, effective human resource management should focus on strengthening these two aspects to improve performance and stability in public organizations.